2015
DOI: 10.1364/ao.54.008166
|View full text |Cite
|
Sign up to set email alerts
|

High-power 1018  nm ytterbium-doped fiber laser and its application in tandem pump

Abstract: In this paper, we present our experimental results of a high-power 1018 nm fiber laser and its usage in tandem pump. A record output power of 476 W 1018 nm fiber laser is obtained with an efficiency of 78.2%. Utilizing a specially designed gain fiber, a one-stage high-power monolithic fiber amplifier tandem pumped by six 1018 nm fiber lasers is assembled. A 110 W 1090 nm seed is amplified to 2140 W, and the efficiency is as high as 86.9%. The beam quality factor M2 is measured to be 1.9. Limitations and possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…In most of present high-power fiber laser systems, laser diodes are used as pump source. Recently, tandem pumping technique, which uses 'fiber laser' to pump active fiber, has been under intensive research, where the brightness of the pump laser is significantly increased [3,[46][47][48][49] . In the present sub-section, we demonstrate the NFA in tandem pumping scheme for the first time.…”
Section: Tandem-pumped High-power Nfamentioning
confidence: 99%
“…In most of present high-power fiber laser systems, laser diodes are used as pump source. Recently, tandem pumping technique, which uses 'fiber laser' to pump active fiber, has been under intensive research, where the brightness of the pump laser is significantly increased [3,[46][47][48][49] . In the present sub-section, we demonstrate the NFA in tandem pumping scheme for the first time.…”
Section: Tandem-pumped High-power Nfamentioning
confidence: 99%
“…Despite most of the high power, narrow-bandwidth fiber amplifiers being pumped by 976 nm laser diodes (LDs) for being favorable of SBS management, tandem pumping is a robust route for simultaneously decreasing the quantum defect and pump absorption for TMI suppression [33,37] . This technique had been widely used in high power fiber amplifiers with broadband spectral characteristics [38][39][40][41][42] , and the output powers had been remarkably scaled to be beyond 3.5 kW power level by several groups [38,41,42] . Due to the small absorption area of the Yb-doped active fiber at 1018 nm, one point should be noted that the suppressions of SBS and stimulated Raman scattering (SRS) are more difficult when tandem pumping is employed in high power, narrow-bandwidth fiber amplifiers.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the 10 kW single-mode fiber lasers developed by IPG photonics were pumped by 1018 nm fiber lasers based on tandem pumping [10]. From then on, the important role of YDFLs operating around 1018 nm attracted much attention for the use of tandem pumping [11][12][13]. After intensive theoretical and experimental investigations, the important rules to build high power 1018 nm YDFLs are well known, which include employing YDF with a high core/inner cladding area ratio, shortening the YDF length, suppressing Fresnel reflection and so on.…”
Section: Introductionmentioning
confidence: 99%